Self-Catalytic Growth of Elementary Semiconductor Nanowires with Controlled Morphology and Crystallographic Orientation - Jang, Hyeon Sik; Kim, Tae Hoon; Kim, Byeong Geun; Hou, Bo; Lee, In Hwan; Jung, Su Ho; Lee, Jae Hyun; Cha, Seungnam; Yang, Cheol Woong; Kim, Byung Sung; Whang, Dongmok (Nano Letters, 2021)
While the orientation-dependent properties of semiconductor nanowires have been theoretically predicted, their study has long been overlooked in many fields owing to the limits to controlling the crystallographic growth direction of nanowires (NWs). We present here the orientation-controlled growth of single-crystalline germanium (Ge) NWs using a self-catalytic low-pressure chemical vapor deposition process. By adjusting the growth temperature, the orientation of growth direction in GeNWs was selectively controlled to the «110», «112», or «111»directions on the same substrate. The NWs with different growth directions exhibit distinct morphological features, allowing control of the NW morphology from uniform NWs to nanoribbon structures. Significantly, the VLS-based self-catalytic growth of the «111»oriented GeNW suggests that NW growth is possible for single elementary materials even without an appropriate external catalyst. Furthermore, these findings could provide opportunities to investigate the orientation-dependent properties of semiconductor NWs.
Keywords: Catalytic growth; Chemical vapour deposition; Germaniums (Ge); Growth directions; Orientation control; Orientation dependent; Property; Self-catalytic; Self-catalytic growth; Semiconductor nanowire; chemical vapor deposition; germanium; nanowire; orientation control; self-catalytic growth